Which cuff should I use? Indirect blood pressure measurement for the diagnosis of hypertension in patients with obesity: a diagnostic accuracy review. Issue 11 (3rd November 2016) - Irving, Greg; Holden, John; Stevens, Richard; McManus, Richard J
Abstract : Objective: To determine the diagnostic accuracy of different methods of blood pressure (BP) measurement compared with reference standards for the diagnosis of hypertension in patients with obesity with a large arm circumference. Design: Systematic review with meta-analysis with hierarchical summary receiver operating characteristic models. Bland-Altman analyses where individual patient data were available. Methodological quality appraised using Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS2) criteria. Data sources: MEDLINE, EMBASE, Cochrane, DARE, Medion and Trip databases were searched. Eligibility criteria: Cross-sectional, randomised and cohort studies of diagnostic test accuracy that compared any non-invasive BP tests (upper arm, forearm, wrist, finger) with an appropriate reference standard (invasive BP, correctly fitting upper arm cuff, ambulatory BP monitoring) in primary care were included. Results: 4037 potentially relevant papers were identified. 20 studies involving 26 different comparisons met the inclusion criteria. Individual patient data were available from 4 studies. No studies satisfied all QUADAS2 criteria. Compared with the reference test of invasive BP, a correctly fitting upper arm BP cuff had a sensitivity of 0.87 (0.79 to 0.93) and a specificity of 0.85 (0.64 to 0.95); insufficient evidence was available for other comparisons to invasive BP. Compared with the reference test of a correctly fitting upper arm cuff, BP measurement at the wrist had a sensitivity of 0.92 (0.64 to 0.99) and a specificity of 0.92 (0.85 to 0.87). Measurement with an incorrectly fitting standard cuff had a sensitivity of 0.73 (0.67 to 0.78) and a specificity of 0.76 (0.69 to 0.82). Measurement at the forearm had a sensitivity of 0.84 (0.71 to 0.92) and a specificity 0.75 of (0.66 to 0.83). Bland-Altman analysis of individual patient data from 3 studies comparing wrist and upper arm BP showed a mean difference of 0.46 mm Hg for systolic BP measurement and 2.2 mm Hg for diastolic BP measurement. Conclusions: BP measurement with a correctly fitting upper arm cuff is sufficiently sensitive and specific to diagnose hypertension in patients with obesity with a large upper arm circumference. If a correctly fitting upper arm cuff cannot be applied, an incorrectly fitting standard size cuff should not be used and BP measurement at the wrist should be considered.